2014
DOI: 10.1371/journal.pone.0085425
|View full text |Cite
|
Sign up to set email alerts
|

Association between Glucocorticoid Receptor Methylation and Hippocampal Subfields in Major Depressive Disorder

Abstract: BackgroundDNA methylation in the promoter region of the glucocorticoid receptor gene (NR3C1) is closely associated with childhood adversity and suicide. However, few studies have examined NR3C1 methylation in relation to major depressive disorder (MDD) and hippocampal subfield volumes. We investigated the possible association between NR3C1 methylation and structural brain alterations in MDD in comparison with healthy controls.MethodsWe compared the degree of NR3C1 promoter methylation in the peripheral blood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 47 publications
(65 reference statements)
5
80
0
1
Order By: Relevance
“…Additionally, changes in the HPA axis induced by childhood trauma and poor parental care perception were related to cocaine use during adulthood (Gerra et al, 2009;Gerra et al, 2010). The robust evidence of epigenetic changes occurring in GR and MR coding genes reinforce the possibility of gene-environmental interactions (Harris et al, 2013;Joels et al, 2008;Lian et al, 2014;Na et al, 2014;van der Knaap et al, 2014;Yehuda et al, 2014aYehuda et al, , 2014b. However, studies designed to evaluate this issue are scarce in crack/cocaine addiction.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, changes in the HPA axis induced by childhood trauma and poor parental care perception were related to cocaine use during adulthood (Gerra et al, 2009;Gerra et al, 2010). The robust evidence of epigenetic changes occurring in GR and MR coding genes reinforce the possibility of gene-environmental interactions (Harris et al, 2013;Joels et al, 2008;Lian et al, 2014;Na et al, 2014;van der Knaap et al, 2014;Yehuda et al, 2014aYehuda et al, , 2014b. However, studies designed to evaluate this issue are scarce in crack/cocaine addiction.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, 8 studies examined the effects of psychopathologies on human GR gene methylation. Specifically, studies included response to stress (51), borderline personality disorder (52), bulimia nervosa (21), post-traumatic stress disorder (PTSD) (5355) and depression (30, 56) (table 3). …”
Section: Resultsmentioning
confidence: 99%
“…However, the results are inconsistent. Whereas several studies have reported hippocampal volumetric reduction in depression (Bremner et al, 2000), differences in hippocampal volume between patients with depression and controls have not been found in other studies (Na et al, 2014a;Vakili et al, 2000). Investigation of other brain regions involved in the regulation of cognition and emotion, such as the prefrontal cortex, the insula, and the occipital cortex, is needed (Price and Drevets, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 98%